Pojęcie i struktura procesu zarządzania ryzykiem ze szczególnym uwzględnieniem ryzyka katastroficznego - Strupczewski, Grzegorz (Conception and Structure of Risk Management Process in Catastrophic Risk, 2008)
The aim of the article is to review existing risk management (RM) theory in the field of general enterprise RM as well as in the specific field of disaster RM. The article begins with a short historical view on the beginning of the RM discipline. After that the general RM concept is defined and the most important RM process theories are presented. Evolutionary changes of the role and importance of RM are also discussed. In the final part of the article disaster RM is defined and analyzed. The author concludes that in the modem "risk culture" of society and the need for providing total security, risk management procedures are the most efficient and practical solution.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 413-419